Oil Extraction and Quality Stability of Crude Palm Oil Derived from Variations in Palm Fruit Ripeness - Ika Ucha Pradifta Rangkuti; Muhammad Syukri; Jenny Elisabeth; Dwita Sari (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Processing palm fruit produces crude palm oil. Crude palm oil levels continue to increase during the fruit ripening process. The parameters used in determining the maturity criteria for palm oil harvest are color change and fruit breaking off from the bunch. Harvest quality is determined by the mature fraction. One of the problems that occurs in palm oil factories is the selection of palm fruit bunches (FFB), which are divided into three classes, namely unripe, ripe and over ripe. Selection of FFB is done manually, namely visually. The quality of palm oil is greatly influenced by the level of ripeness of the fruit at the time of harvest and post-harvest handling until the mill. This research aims to evaluate the use of variations in palm fruit maturity used in PKS which are related to yield and quality as well as oxidative stability and color. The research results showed that the variation in palm fruit maturity used resulted in the highest yield, namely 17% in P2. The quality of crude palm oil obtained from variations in fruit maturity shows different results, where the highest free fatty acid content of 2.57% is located in P2, namely a mixture of ripe and overripe fruit, while the highest water content is found in P2, namely 0.65 %. P3 has the highest impurity content of 0.68%. The oxidative stability and color obtained from using variations in fruit maturity that were heated for 24 hours decreased in value to red and yellow